Steroid therapy – advantages and risks - Horst-Sikorska, Wanda (Przewodnik Lekarza/Guide for GPs, 2008)
Glucocorticosteroid hormones are common drugs. Their importance is due to their anti-inflammatory, anti-allergic, antipruritic and immunosuppressive actions. They are applied in many clinical disciplines as topical or systemic acting drugs and using different routes of administration: topical, enteric, and parenteral. They are used in acute or chronic conditions. They are first-line treatments in oncology, haematology and organ transplants. They save lives in acute shock reactions. Beside the benefits there are also side effects, which cannot be neglected. Each therapy must be considered regarding its advantages and disadvantages. There is no totally safe steroid dose and no administration route without side effects.